Concept Maps and Meaningful Learning in Primary School Students - Maraza-Vilcanqui, Beker (2022)
Objective. This research article aimed to determine the level of significant learning acquired by students in the third grade of Primary Education after applying concept maps in the teaching process. Methodology. Research of quantitative approach, experimental type, with a quasi-experimental design and a sample of 66 students, using the pre-test and post-test as data collection instruments. Analysis of Results. The results obtained allowed determining that most of the students in the experimental group developed their intellectual capacities, explored their knowledge, and, finally, achieved competencies and skills at a high and significant level. Conclusions. The application of concept maps in the teaching process allows teachers to present information in a summarized form so that students can easily grasp key ideas and remember them for life, thus helping to improve student learning. Hence, its use is recommended from the early years of school.